2013
DOI: 10.3389/fpsyg.2013.00679
|View full text |Cite
|
Sign up to set email alerts
|

The added value of eye-tracking in diagnosing dyscalculia: a case study

Abstract: The present study compared eye movements and performance of a 9-year-old girl with Developmental Dyscalculia (DD) on a series of number line tasks to those of a group of typically developing (TD) children (n = 10), in order to answer the question whether eye-tracking data from number line estimation tasks can be a useful tool to discriminate between TD children and children with a number processing deficit. Quantitative results indicated that the child with dyscalculia performed worse on all symbolic number li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 39 publications
3
34
0
2
Order By: Relevance
“…Eye movement recording yields access to the infant's mind or provides information about specific task strategies that cannot be extracted from response times or error rates alone (Bahnmueller et al, 2016;Ganor-Stern and Weiss, 2016;Macci Cassia et al, 2016;Van't Noordende et al, 2016). Moreover, the studies reported here shed new light on the temporal development of spatial-numerical associations during single number processing and arithmetic performance (Hartmann et al, 2016;Myachykov et al, 2016;Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Eye movement recording yields access to the infant's mind or provides information about specific task strategies that cannot be extracted from response times or error rates alone (Bahnmueller et al, 2016;Ganor-Stern and Weiss, 2016;Macci Cassia et al, 2016;Van't Noordende et al, 2016). Moreover, the studies reported here shed new light on the temporal development of spatial-numerical associations during single number processing and arithmetic performance (Hartmann et al, 2016;Myachykov et al, 2016;Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…The knowledge of successful task strategies derived from eye movement analyses (cf. Ganor-Stern and Weiss, 2016;van't Noordende et al, 2016) might then be used for the development of training interventions; in turn, the success of these interventions can then be determined through eye-tracking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, however, Haase et al (2014) concluded that subtypes of MLD may not only be associated with content-related deficits but also more general impairments of information processing should be considered. In line with this view, Van Viersen et al (2013) suggested that evaluating eyefixation behavior may provide interesting new insights into the mechanisms underlying DD. In their Opinion, Kaufmann et al (2013) argue that MLD/DD is a heterogeneous disorder resulting from individual differences in development or function at neuroanatomical, neuropsychological, behavioral, and interactional levels.…”
mentioning
confidence: 84%
“…In future research, interviews and observations with children regarding their number line estimations would give an additional contribution to the field which could provide new perspectives on and immerse our understanding about children's number line estimates and representations of number (see also Peeters et al 2015). Further, eye-tracking (Schneider et al, 2008;van Viersen, Slot, Kroesbergen, van't Noordende, & Leseman, 2013) could also be used to confirm the use of reference points and possible additional referents assumed to influence children's number line estimations.…”
Section: Implications and Suggestions For Future Researchmentioning
confidence: 99%